1989
DOI: 10.1103/physrevb.40.1257
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigations of CdS at high pressure

Abstract: The photoluminescence spectrum and absorption spectrum as well as resonant Raman scattering tuned by pressure in heavily doped CdS have been studied. The pressure coefficients of shallow levels (I~and I,) and deep levels (G, and R) are measured. A new optical-absorption method under pressure was developed and the shift of band gap with pressure of CdS in the direct-band-gap wurtzite phase and indirect-band-gap rock-salt phase was measured. From the experimental results of resonant Raman scattering tuned by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…Corll reported that the phase transition pressures are very approximately at 3.1 GPa (ZB-RS), 2.5 GPa (WZ-RS), and 2.8 GPa (WZ-ZB mixes -RS), respectively [10]. Using the resonant Raman scattering tuned by pressure, Zhao et al and Venkateswaran et al reported that the phase transition of CdS from a direct-gap WZ to an indirect-gap RS-structure at about 2.7 GPa [11] and 2.5 GPa [12]. Knudson et al investigated the WZ-RS phase transition of CdS using picosecond time-resolved electronic spectroscopy in plate impact shock wave experiments [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corll reported that the phase transition pressures are very approximately at 3.1 GPa (ZB-RS), 2.5 GPa (WZ-RS), and 2.8 GPa (WZ-ZB mixes -RS), respectively [10]. Using the resonant Raman scattering tuned by pressure, Zhao et al and Venkateswaran et al reported that the phase transition of CdS from a direct-gap WZ to an indirect-gap RS-structure at about 2.7 GPa [11] and 2.5 GPa [12]. Knudson et al investigated the WZ-RS phase transition of CdS using picosecond time-resolved electronic spectroscopy in plate impact shock wave experiments [13].…”
Section: Introductionmentioning
confidence: 99%
“…During the past few decades, the investigations of phase transitions have attracted considerable attention by experiments [8][9][10][11][12][13][14][15]. The pioneering study of optical-absorption edge of CdS under pressure indicated that the phase transition (WZ-RS) occurs at about 2.7 GPa [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the value of Ut(PT)-UiP T ) itself is not 8 known, it can be calculated from known quantities. By equating the chemical potentials in equation 1, it is possible to obtain the expression (6) where P B is the bulk phase transition pressure of 3.0 GPa. As the changes in U with pressure can be calculated by integrating the pressure volume curves for each phase, equation 5 can now be rewritten as…”
Section: (5)mentioning
confidence: 99%
“…Deep levels in CdS have been previously studied using a number of characterization techniques including DLTS [1][2][3], thermally stimulated current (TSC) [4], photoconductivity [5][6][7], photoluminescence [1,8] and PICTS [9,10]. Energy levels in the range 0.033-1.3 eV have been reported.…”
Section: Introductionmentioning
confidence: 99%